Application of individualized osteotomy and registration guide plate in temporomandibular joint gap arthroplasty: a pilot clinical study - Zhang, Jianfei; Sun, Jian; Jiang, Tengfei; Zhou, Guokai; Tian, Yuan; Xia, Liang; Zhang, Wenbin (Frontiers in Oral Health, 2025)
IntroductionTemporomandibular joint (TMJ) ankylosis severely compromises mandibular mobility and overall oral function. Gap arthroplasty remains the standard surgical treatment. However, the accuracy of navigation-assisted procedures is frequently limited by anatomical registration challenges, particularly when relying on dental surface matching.MethodsThis single-center prospective study enrolled 30 patients with unilateral bony TMJ ankylosis. Participants were randomly assigned to either a dental surface registration group (n = 18) or a guide plate registration group (n = 12). The patient-specific guide plate integrated both osteotomy slots and fiducial markers. Primary outcomes included registration time and target registration error (TRE). Secondary outcomes were operative time, mouth opening at three months, and perioperative complications.ResultsThe guide plate group achieved significantly shorter registration times (56.23 ± 11.33 s; 95% CI: 49.35–63.11) compared with the dental registration group (935.03 ± 85.40 s; 95% CI: 894.55–975.51; P < 0.001). TRE was also significantly lower in the guide plate group (0.69 ± 0.10 mm; 95% CI: 0.62–0.76) than in the dental registration group (2.82 ± 0.45 mm; 95% CI: 2.60–3.04; P < 0.001). Average operative time was reduced in the guide plate group (124.63 ± 5.39 min; 95% CI: 121.44–127.82) compared with the dental group (134.31 ± 12.76 min; 95% CI: 128.10–140.52; P = 0.009). Postoperative mouth opening at three months was comparable between groups (31.5 ± 4.23 mm; 95% CI: 28.94–34.06 vs. 31.33 ± 3.34 mm; 95% CI: 29.65−33.01; P = 0.905). No major intraoperative or postoperative complications were observed.DiscussionIntegration of an individualized osteotomy and registration guide plate significantly improved intraoperative efficiency and spatial accuracy in TMJ gap arthroplasty without compromising functional outcomes. These pilot findings support the clinical feasibility of the guide plate system, though larger multicenter studies and evaluation of inter-operator variability are required for broader validation.